Political Risk and Market Reaction: Abnormal Return of the Indonesian Stock Exchange (IDX) During the 2025 Demonstration Event - Dodi Siswanto; Agus Rohiman (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the Indonesian capital market's reaction to the political demonstrations on August 29, 2025, as a form of non-electoral political risk that could potentially impact stock market performance. In the context of increasing financial market sensitivity to socio-political uncertainty, this study uses a quantitative explanatory approach with an event study method to test for abnormal returns (AR) and cumulative abnormal returns (CAR) on the Indonesian Stock Exchange (IDX) during the observation period. Secondary data were obtained from the daily closing prices of the IDX with an estimation window from July 1 to August 22, 2025, and a seven-day event window surrounding the event. The analysis results show that although no significant abnormal returns were found on the day of the event, there was a statistically significant negative cumulative abnormal return during the observation period, indicating that the political demonstrations exerted accumulative pressure on the stock market. These findings indicate that the Indonesian capital market reacts negatively to non-electoral political events, with an indirect and cumulative adjustment pattern, reflecting the characteristics of an emerging market with semi-strong efficiency. This research contributes to expanding the literature on political risk in emerging markets and provides practical implications for investors and policymakers to strengthen risk mitigation strategies and maintain market stability amidst domestic political uncertainty.